2023
DOI: 10.1021/acsomega.3c00973
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Investigation on Spontaneous Imbibition of Surfactant Mixtures in Low Permeability Reservoirs

Abstract: Spontaneous imbibition of surfactants could efficiently enhance oil recovery in low permeability sandstone reservoirs. The majority of studies have considered the application of individual surfactants to alter wettability and reduce interfacial tension (IFT). However, a significant synergistic effect has been reported between different types of surfactants and between salts and surfactants. Therefore, this study systematically studied the capability of a binary surfactant mixture (anionic/nonionic) and a terna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Through immersion experiments, Begum found that immersion solutions with low IFT are absorbed more and their recovery factors were high . Wang investigated SI of different surfactant mixtures and found that the smaller the IFT, the smaller the value of the work from adhesion thus producing a higher recovery factor . Finally, a part of people believe that there is an optimal critical value of the IFT.…”
Section: Introductionmentioning
confidence: 99%
“…Through immersion experiments, Begum found that immersion solutions with low IFT are absorbed more and their recovery factors were high . Wang investigated SI of different surfactant mixtures and found that the smaller the IFT, the smaller the value of the work from adhesion thus producing a higher recovery factor . Finally, a part of people believe that there is an optimal critical value of the IFT.…”
Section: Introductionmentioning
confidence: 99%